UV-cured TiO2 electron transport layers for printable solar cells. Issue 71 (13th July 2016) - Heinrichova, Patricie; Dzik, Petr; Tkacz, Jakub; Vala, Martin; Weiter, Martin
Abstract : This article is focused on the development of new formulations of inks for low-temperature deposition of printed electron transport layers based on titanium oxide. Abstract : This article is focused on the development of new formulations of inks for printed electron transport layers based on titanium oxide. The electron transport layers were prepared from a suspension consisting of titania nanoparticles and a novel organo-silica binder. The layers are post-processed by low temperature UV curing instead of thermal annealing. The UV-cured TiO2 layers were applied in inverted-structure organic bulk heterojunction solar cells with the active layer from a PCDTBT : PC60 BM blend. These devices achieved a power conversion efficiency comparable to devices with TiO2 layers prepared by the common sol–gel process relying on high-temperature calcination. Thus the novel UV curable TiO2 formulation is promising as printable electron transport layers for flexible devices, which are not compatible with thermal processing.